Elastic–Plastic Fracture Analysis on Defective Q345 Steel in the Process of Small-Scale Creep Crack Propagation - Huajing Guo; Wenjie Tang; Xiaolong Tong; Bin Sun (Buildings)
Q345 steel is usually used on structures working under high temperature where creep deformation could endanger their structural integrity. In order to support the application of steel structures made of Q345 under high temperature, a fracture analysis on defective Q345 steel in the process of small-scale creep crack propagation has been performed. Three-dimensional finite element models with a semi-elliptical surface crack have been established, and the crack propagation process of Q345 steel has been simulated at 400 °C. The constraint effect near the crack tip in the process of creep crack propagation has been analyzed using the J-A2 two-parameter method in which the influence of the crack aspect ratio, loading level, and biaxial loading ratio was studied. The previously developed constraint-based R6 procedure was adopted to assess the structural integrity of the cracked structure under small-scale creep conditions. The results showed that small-scale creep crack propagation behavior exhibits great influence on both crack tip fields and a constraint effect near the crack tip. The increase in the biaxial loading ratio, loading level, and aspect ratio of the crack could lead to an increase in the J integral, an enhancement of the constraint effect, and a decrease in the safe area in the failure assessment diagram for the cracked structure in the process of small-scale creep crack propagation.